BUMDesa Policy Innovation to Increase Village Authenticity in a Neo-Institutionalism Perspective - Jairi Irawan; Bintaro Wardiyanto; Erna Setijaningrum (Faculty of Law, University of Merdeka Malang, 2023)
This study aims to identify policy innovations in BUMDesa and their contribution to increasing village original income (PADesa). This study uses exploratory qualitative methods through in-depth interviews with actors who are directly involved with BUMDesa Larasati and related external parties. The results of the research were then analyzed using the perspective of Neo-Institutionalism. This study found that the policy innovations formulated and implemented by BUM Desa Larasati were inseparable from the role of critical actors within the Village Head of Kendalbulur. The Village Head has full support from internal BUMDesa and the Village Consultative Bodyâ€”in addition to interactions with external institutions such as the Tulungagung DPMD, Banking, and PT. POS, East Java Village BUM Clinic, makes it easy to make policies. Policy innovation has significantly increased PADesa in the last three years. BUM Desa Larasati is already a legal entity and is ready to compete with other agencies. For this reason, synergy is needed between OPD and the private sector regarding assistance to BUM Desa so that human resources and their existence are properly maintained.How to cite item: Irawan, Jairi, Bintoro Wardiyanto, and Erna Setijaningrum. â€œBUMDesa Policy Innovation to Increase Village Authenticity in a Neo-Institutionalism Perspective.â€ Jurnal Cakrawala Hukum. 14 no. 1 (2023):9-20. DOI: 10.26905/idjch.v14i1.9871.